2013
DOI: 10.5005/jp-journals-10024-1314
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Oil—A Biofriendly Substitute for Xylene in Deparaffinization: A Novel Method

Abstract: The study recommends refined mineral oil as a biofriendly and effective xylene substitute in deparaffinization of tissue sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
14
0
3
Order By: Relevance
“…evaluated the efficacy of mineral oil over xylene in routine H and E staining and found that 93.3% sections were adequate for diagnosis. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the efficacy of mineral oil over xylene in routine H and E staining and found that 93.3% sections were adequate for diagnosis. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Owing to this, there has been a continuous search for bio-safe substitutes for xylene. [3][4][5][6][7][8][9] Any attempt to reduce the health hazards in histopathology laboratories provides scope for a trial. Hence, this study was attempted to assess the role of bleached vegetable oil (palm oil) as a suitable alternative to xylene in processing of oral mucosal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are striving attempts reported in English literature, searching for biosafe alternatives for this sweet-smelling toxic substance; Mineral oil mixture, vegetable oil, cedar wood oil, and liquid dish washing soap are a few to name. [3][4][5][6][7][8][9] Vegetable oils like palm oil are saturated fat that exist as semisolids at room temperature. [10] Conversion of a vegetable or plant-based food into oil involves complicated chemical process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] Occupational safety and health administration (OSHA) regulation identified xylene as a biohazardous chemical and the need for a safer nontoxic substitute increases. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Premalatha et al . [ 5 ] also used mineral oil as a deparaffinizing agent and Ananthaneni et al [ 9 ] attempted to use lemon water as a dewaxing agent.…”
Section: Introductionmentioning
confidence: 99%